The Reality Of Healthy Nutrition In The Muscular Development Among Bodybuilders - Mohammed, cherif Mahdi; Mohamed, Arafa; Mohamed, Negaz (Journal of Sport Science Technology and Physical Activities, 2021)
The study aimed to know the reality of healthy nutrition in the muscle development of bodybuilding practitioners, and for this purpose we used the descriptive approach on a sample of 100 university students involved in bodybuilding clubs, chosen in an intentional way, and to collect data we used the questionnaire, and the results concluded that bodybuilding practitioners do not have full awareness of rational consumption in their diets that they eat daily for the sake of muscle development, that bodybuilding practitioners are not aware of the basics of distributing the training load in the sports program that they follow during training sessions for muscle development, and from this we can say that the reality of healthy nutrition in muscle development for bodybuilding practitioners is still far from the correct practice.